Impact Organizational Culture on Organizational Commitment Study of Banking Company in Indonesia - Rezi Muhamad Taufik Permana (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
Organizational culture is no longer seen as a legacy of the past is seen as a mere, but also must be designed and deployed as a strategic tool to achieve corporate objectives. Culture is also an indicator to see how committed an employee of the company. Using a questionnaire survey, this paper examined effected of corporate culture on organizational commitment. Specifically, this paper examines four dimensions of corporate cultures, the teamwork, communication, rewards and recognition, and training and development of employee commitment to the organization. One hundred and fifty-six respondents from banking companies to be a part of this survey. The research hypothesis was tested using multiple hierarchical regression analysis. The results showed that all dimensions of corporate culture that are selected in this study can use as a determinant/indicator of organizational commitment.